Implementasi Manajemen Perpustakaan untuk Meningkatkan Minat Baca Siswa - Sintasari, Beny; Albaina, Fira (Islamic Education Management Study Program of STIT al Urwatul Wutsqo Jombang, East Java, Indonesia, 2024)
This research aims to analyze the implementation of library management in increasing students' reading interest. The method used is descriptive qualitative, with data collection techniques through observation, interviews and documentation. The research results show that library management includes several strategic steps. First, library planning focuses on creating an environment that supports learning and is fun for students. Second, organizing involves librarians and technical teams working synergistically to ensure library services run efficiently and effectively. Third, regular evaluations are carried out to ensure the library functions optimally as a learning resource center. This evaluation aims to identify areas that require improvement and innovation, so that the library continues to develop according to user needs. Library services to increase interest in reading include providing interesting reading materials, active promotions, book lending competitions, study tours, awards for active borrowers, reading records, and receiving suggestions for improvement.